Design of three-axis square Helmholtz coils for compact atomic magnetometer - Kittipong Panthinuan (2020)
© 2020 SPIE. Compact atomic magnetometer (AM) has potential applications in biomedical devices to measure magnetic signals from human organs, e.g. magnetocardiography and magnetoencephalography. Reducing the size of Helmholtz coils is an essential step for a design of compact AM, which also leads to lower cost in manufacturing processes. However, the homogeneity and magnitude of the magnetic fields and the size of a rubidium vapor cell must be considered for the decrease of the coil size. Here, we report a design of compact AM with square Helmholtz coils of 24×24×24 cm3 housing a rubidium vapor cell of 7.5 cm in length. The coils were calculated to induce a constant magnetic field of 0.5 gauss covering the length of 10 cm along the axis of symmetry of the coils. The field gradient was measured to be less than 4% of the magnitude over the distance of 6 cm. For zero-field condition, the field gradient was no more than 1 mgauss in all axes. Further developments of square Helmholtz coils for improving the field gradients are still needed before implementing in the compact AM.